Symbiosis - Cid Rigobelo, Everlon (IntechOpen, 2018)
Over the last few decades, the prevalence of studies about symbiosis has dramatically grown in most regions of the world. Many aspects have been investigated related to this phenomenon. If we can gain understanding about symbiosis, then we may be able to manipulate it to reduce both chemical fertilizer use and environmental impact without decreasing the yield. This book provides information about the symbiotic relationship between a fern and Azolla, plant control over thread development during legume-rhizobia symbiosis, bacterial leaf nodule symbiosis in flowering plants and the potential of rhizobium strains in improving nitrogen fixation and legume yields. We hope this information will be useful to all people working on a hot topic.